Root Distribution Pattern in Dalbergia sissoo Roxb. under Different Root Management Practices in Agrisilvicultural System - Newaj, Ram; Solanki, K.R.; ., Ajit; Handa, A.K.; Shanker, A.K. (Indian Journal of Agroforestry, 2020)
An observation on rooting patterns in Dalbergia sissoo Roxb. under different management practices viz. deep ploughing, root barrier (polythene sheet), deep basin (sunken method), pruning up to 40 % height of the tree, growth regulator (GA3 100 ppm) and control in agrisilvicultural system was made to a depth of 105 cm and laterally to 3.0 m from the tree base to study the effect of management practices on concentration of roots. Deep basin and deep ploughing were quite effective to restrict the movement of roots on an upper surface of the soil and these two practices resulted in lower number of roots and their density in top 30 cm soil as compared to other practices. In general, maximum concentration of roots (76 to 84% of the total root) was found on top 30 cm soil and concentrated near to the tree base with a sharp decline with increase in to soil depth and distances from the tree base. The major parts of the roots were confined up to 60 cm soil depth and in 75-105 cm soil depth the roots were negligible. The root density also showed a similar trend at different depth and distances from tree base. Root weight ranged from 22.71 to 24.16 per cent of total biomass under different management practices at four years age. But root biomass was less in deep basin and deep ploughing treatment. The root competition may be avoided for some more time through deep basin and deep ploughing which may be a regular practice to destroy the roots on an upper surface in agroforestry systems.